Estimation of Salivary and Serum Lactate Dehydrogenase (LDH) Levels in Individuals with Oral Cancer, Oral Potentially Malignant Disorders, Tobacco Users, and Healthy Subjects – A Pilot Study - Mohithan Subramanian; Saramma Mathew Fenn; Gowda Venkatesha Ramachandra Reddy; Karthik Rajarammohan; Ravikumar Pethagounder Thangavelu (Journal of Indian Academy of Oral Medicine and Radiology)
Background: Oral cancer represents a major global health concern, accounting for approximately 11 million new cases and over 6 million deaths annually. Early detection and accurate prediction of metastasis are critical in improving outcomes. Objectives: To evaluate serum and salivary LDH levels and their correlation among oral cancer patients, potential malignant disorders, tobacco users, and healthy individuals. Methods: The study divided 120 participants into four groups: Group A (oral cancer), Group B (potentially malignant disorders), Group C (tobacco users), and a control group of 30 healthy individuals. Saliva and serum samples (2 ml each) were collected, stored at -20°C, and analyzed within 24 hours following centrifugation. Both serum and saliva were analyzed using an LDH kit (Liquizyme) on a semi-auto analyzer. Following the collection of values, statistical analysis was conducted using one-way ANOVA and Pearson’s correlation. Results: One-way ANOVA revealed significant differences in salivary LDH levels among groups (Controls: 82.00 IU/L, Tobacco users: 106.97 IU/L, Potentially malignant group: 157.23 IU/L, Oral cancer group: 193.73 IU/L, P < 0.05). Pearson’s correlation indicated positive correlations in oral cancer (r = 0.1295), potential malignant disorder (r = 0.0961), and healthy individuals (r = 0.2402), while tobacco users showed a negative correlation (r = -0.0849). Conclusion: The study has shown that salivary LDH is preferable to serum LDH for early detection and monitoring, showing significant elevation in oral cancer and potentially malignant disorders, with the advantage of non-invasive method of collection.